2010
DOI: 10.1021/jf103085p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Industrial and Alternative Farming Systems on Contents of Sugars, Organic Acids, Total Phenolic Content, and the Antioxidant Activity of Red Beet (Beta vulgarisL. ssp.vulgarisRote Kugel)

Abstract: The contents of sugars, organic acids, total phenolic content, and the antioxidant activity were quantified in the flesh of red beet from conventional (CON), integrated (INT), organic (ORG), biodynamic (BD), and control farming systems using established methods. Significant differences were measured for malic acid, total phenolic content (TPC), and total antioxidant activity, where malic acid content ranged from 2.39 g kg(-1) FW (control) to 1.63 g kg(-1) FW (CON, ORG, and INT). The highest TPC was measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(90 citation statements)
references
References 37 publications
(45 reference statements)
15
71
0
Order By: Relevance
“…Only one eggplant cultivar among three and in 1 year along 2 years exhibited a higher polyphenols content under organic management [81], while no differences were found from eggplant fruits harvested in different locations under conventional and organic farming [82]. Biodynamic cultivated red beets had a higher polyphenol content than conventional and integrated ones [83] so as biodynamic lettuce leaves which exhibited a higher polyphenols content than conventional and organic ones [84]. In the case of cabbage internal leaves with four samplings from November to January, only for one sampling date, conventional grown plants exhibited a higher polyphenols content, while in the three other dates the opposite occurred [85].…”
Section: Effect Of Managementmentioning
confidence: 92%
“…Only one eggplant cultivar among three and in 1 year along 2 years exhibited a higher polyphenols content under organic management [81], while no differences were found from eggplant fruits harvested in different locations under conventional and organic farming [82]. Biodynamic cultivated red beets had a higher polyphenol content than conventional and integrated ones [83] so as biodynamic lettuce leaves which exhibited a higher polyphenols content than conventional and organic ones [84]. In the case of cabbage internal leaves with four samplings from November to January, only for one sampling date, conventional grown plants exhibited a higher polyphenols content, while in the three other dates the opposite occurred [85].…”
Section: Effect Of Managementmentioning
confidence: 92%
“…Higher values of antioxidant activity in organic fruit were also reported by Wang et al (2008) and Vrček et al (2011). Bavec et al (2010) and Borguini et al (2013) found higher antioxidant activity in organic vegetables as compared to conventional. In our study statistically significant differences in the EA AA of LSMs between farming systems for vegetables were estimated only for broccoli (p < 0.05), cucumber (p < 0.05) and rocket (p < 0.01) (Figure 1).…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Type of farming system may also affect the chemical composition of foodstuffs, especially on those that originate from the use of chemical fertilizer and pesticides (Dangour et al, 2009). Organic farming represents a production system, looking for harmony between the environment and the agriculture production (Casado and de Molina, 2009;Bavec et al, 2010). It excludes the use of synthetic fertilizers and pesticides, plant growth regulators and genetically modified organisms (Singh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the increase in compared to their conventional counterparts. The differences concern mainly higher sensory quality of organic fruits and vegetables, as well as the higher content of polyphenolic compounds and vitamins in organic agricultural crops compared to conventional ones (Asami et al, 2003;Bavec et al, 2010;Hallmann and Rembiałkowska, 2012;Średnicka-Tober et al, 2013;Kazimierczak et al, 2014). This is mainly due to different fertilization and crop protection regimes used in organic and conventional production systems.…”
Section: Introductionmentioning
confidence: 99%